EXPLORING HIGHER EDUCATION TEACHERS' SELF-PERCEIVED DIGITAL LITERACY AND ITS CONTRIBUTION TO THEIR DIGITAL IDENTITY ON SOCIAL NETWORKING SITES - Asmin, Arny Irhani; Retnaningdyah, Pratiwi; Mustofa, Ali (NextGen Education Review Journal, 2024)
This study investigates the self-perceived digital literacy competencies of college English teachers and explores how these competencies shape their digital identities on social networking sites (SNSs). This research is considered important in an era where the integration of technology in education and the use of SNSs for professional and personal purposes are increasingly prevalent. Through a comprehensive examination of teachers' self-perceptions and practices on SNS, this study highlights the complex interplay between digital competencies and digital identity construction. Data were collected through in- depth interviews and observations on lecturers' social media content, which provided valuable insights into the role of digital literacy in educators' digital identity. Findings highlighted that although these teachers generally demonstrated moderate digital literacy, they were able to create and develop positive and professional identities on social media. These skills empowered them to engage effectively in online educational communities, interactions, and networks. In addition, the teachers also demonstrated digital competence, confidence, and awareness of their professional responsibilities.